Study of major aromatic compounds in port wines from carotenoid degradation - Ferreira, Antonio César Silva (2010)
The carotenoids degradation and the formation of volatiles were examined by simulating Port wine aging. A two year old red Port wine was saturated with oxygen, supplemented with lutein and b-carotene and kept at 60ºC during 87 h. A similar study was performed in a model wine solution. Results showed that the percentage decrease in lutein levels was, respectively, 79% and 95%, in the wine model solution and in the Port wine, and 55% and 10% for b-carotene, indicating that lutein was more sensitive to degradation than b-carotene. Two other unknown degradation carotenoid compounds were identified by HPLC/DAD (reverse phase λmax: 422; 445; 475 and 422; 445; 472) in the lutein supplemented wine. Levels of b-ionone and b-cyclocitral increased (2.5 times) in both, wine and wine model solution, supplemented with b-carotene. Along with these compounds, the same behaviour was observed in b-damascenone in the supplemented lutein wine and wine model solution. New insights were provided into the understanding of aroma modifications occurring during Port wine aging. The relationship between carotenoid molecules (b-carotene and lutein) and some volatiles has also been provided.